Burn-in testing its quantification and optimization - Kececioglu, Dimitri (Prentice Hall PTR, 1997)
When scientifically planned and conducted, burn-in testing offers one of the most effective methods of reliability screening at the component level. By testing individual elements under constant temperature stress, electrical stress, temperature cycling stress, or a combined thermal-electrical stress, burn-in testing can identify discrete faults that may be harder to perceive at the assembly, module, or system level. This book covers all aspects of burn-in testing, from basic definitions to state-of-the-art concepts. Drawing on a broad database of studies, Burn-In Testing emphasizes mathematical and statistical models for quantifying the failure process, optimizing component reliability, and minimizing the total cost. Vividly illustrated with figures, tables and charts, Burn-In Testing includes: * Definitions, classifications, and test conditions * A review of failure patterns during burn-in * Seven general mathematical models including four bathtub curve models * A quick calculation approach for time determination * Representative cost models and burn-in time optimization * The bimodal mixed-exponential life distribution applied to quantify and optimize burn-in * The Mean Residual Life (MRL) concept applied to quantify and optimize burn-in * The Total Time on Test (TTT) transform and the TTT plot applied to quantify and optimize burn-in * Accelerated testing and its quantification * A roadmap for practical applications With each chapter, Burn-In Testing also offers the appropriate FORTRAN code for the processes described. Burn-In Testing is ideal for practicing engineers in the fields of reliability, life testing, and product assurance. It is also useful for upper division and graduate students in these and related fields.